Penerapan Model Koopertif Tipe Think Pair Share Untuk Meningkatkan Hasil Belajar Siswa Mata Pelajaran IPA Materi Perubahan Sifat Benda Pada Siswa Kelas V SDN Banaran 1 Kediri Tahun Pelajaran 2016 / 2017 - Mariyati, Nina (Universitas Nusantara PGRI Kediri, 2018)
Background problem in this research is result of study of student of class V on science subjects in basic competence concludes result of investigation about change of nature of object show less optimal result. Of the 28 students: the KKM score was 75 new students (39: 28%) while the students who had not reached the KKM score were 17 students (60.71%). One effort that can be done by teacher to answer the above problem is by applying cooperative learning model of Think Pair Share type supported by image media in science learning. The purpose of this research is to know the improvement of science learning outcomes through the implementation of cooperative model of Think Pair Share type with the image media on the students of class V SDN Banaran 1 Pesantren Kediri District Semester I Year Lesson 2016/2017. This type of research is a classroom action research. The subjects studied were the students of grade V of SDN Banaran 1 Kecamatan Pesantren Kediri. The result of data analysis showed that there is an increase of science learning result by applying cooperative model of TPS type with image media. It is visible on; (1) mastery learning; pre cycle 39,29%, cycle 160: 71%, cycle II 89,29%. (2) Average grade; pre cycle 66,78, cycle I 74,64, and cycle II 81,74. (3) Minimum score; pre cycle 40, cycle I 50, and cycle II60. (4) maximum score; pre cycle 90, cycle I 100, and cycle II 100. Thus it can be concluded that the implementation of cooperative model type Think Pair Share with image media can improve the learning outcomes of science in grade V SDN Banaran 1 District Pesantren Kediri City Year I 2016 / 2017. Based on the results of this study suggested that the model of cooperative Think Pair Share type needs to be socialized to teachers and applied in science learning especially to improve student learning outcomes. Further research is done as self-development so as to develop research in a wider scope.